The expression levels of Mir-146b and Mir-221 in thyroid carcinoma tissues and their correlation with malignancy degree - Tan, Dandan; Cui, Yan; Bao, Jing; Xu, Fenlan; Ma, Junfeng (Cellular and Molecular Biology, 2020)
This experiment aimed to investigate the correlation between the expressions of mir-146b and mir-221 and the proliferation, invasion, and malignancy of tumor cells. For this purpose, 135 patients with thyroid cancer treated in our hospital and 120 patients with non-malignant thyroid cancer in the outpatient clinic were selected as subjects. Fine needle biopsy tissues of the two groups were taken as samples to detect the expression levels of mir-146b and mir-221 in the tissues. The effect of the two microRNA on the proliferation and migration of cancer cells was observed by the transfection of cell lines. The contents of gal-3 and MMP9 in serum were further detected, and their relationship with the expressions of mir-146b and mir-221 was analyzed. The results showed that the expressions of mir-146b and mir-221 were significantly decreased and increased in thyroid carcinoma fine-needle aspiration tissues. Mir-146b inhibited the proliferation and migration of cancer cells, while mir-221 promoted this process. In the more cancer cells, the expression levels of these two genes changed more, and the serum levels of gal-3 and MMP9 also increased. It was concluded that the expression levels of mir-146b and mir-221 were correlated with the degree of tumor malignancy, and the low expression of mir-146b and the high expression of mir-221 were correlated with the proliferation, invasion, and malignancy of thyroid cancer tumor cells.